Tatbīq al-manhaj al-durūsī fī taʿlīm al-lughah al-ʿArabīyah lil-dawrah al-mukhṭaṣṣah bimarkaz al-dawārāt wa al-tadribāt jāmiʿat Dār al-Salām Gontūr - Yoke Suryadarma (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This study aimed to describe and analyze in depth about the application of the Arabic language education curriculum which conducted through an intensive course program by the Education and Training Center in University of Darussalam Gontor. This was a field research using qualitative approach. The data were collected by using observation, interviews and documentation. In analyzing the data, it used Miles and Huberman techniques. The results of this study showed that the intensive, effective and efficient training was conducted for trainees from various levels, involved basic, intermediate and high levels. This course used a communicative approach, particularly direct method. The participants lived in a student dormitory with a language habit in the environment for 24 hours. This intensive course aimed to improve receptive language skills including listening and reading, and deductive language skills including writing and speaking. The curriculums of this Education and Training Center consisted of academic and non-academic. Academic curriculum consisted of learning durūs al-lugah al-abiarabiyyah, nahwu and ṣaraf, mahārah kitābah, qirāah, istima ’, and kalām. While the non-academic curriculum was learning vocabulary, watching Arabic films, muhadatsah, singing Arabic songs, speeches, khot, and turats study.